Community-based disaster mitigation in Sinambela Village, Humbang Hasundutan District, North Sumatra Province [Mitigasi bencana berbasis masyarakat di Desa Sinambela Kabupaten Humbang Hasundutan Provinsi Sumatera Utara] - Syahputra, Orang Kaya Hasnanda; Samsuri, Samsuri; Hakim, Lutfi; Fadhilla, Suri (Buletin Pengabdian, 2025)
Sinambela Village has a high potential for geological and hydrometeorological disasters. This is influenced by the biophysical conditions of the village. A significant portion of the community in Sinambela Village is not yet well educated about natural disasters and disaster mitigation. Therefore, disaster mitigation efforts are necessary, considering that floods and landslides have previously struck Simangulampe Village in Bakti Raja Sub-District, which is in the same district as Sinambela Village. This incident occurred on December 1, 2023, resulting in 12 people missing and one confirmed fatality. The primary cause of the flooding was heavy rainfall. In addition to hydrometeorological factors, flooding in Sinambela Village was also caused by various other factors, including sedimentation in the downstream section of the river, reduced vegetation cover in the upstream area, and river channel narrowing. Based on the situational analysis and the challenges faced by the community, it is crucial to build a society that is prepared for disasters, capable of anticipating them, and able to adapt to them an effort known as disaster mitigation. The proposed solution involves community involvement in disaster planning, emergency response, and post-disaster recovery. This community-based initiative is known as Disaster-Resilient Village (DESTANA). Given the increasing risks and challenges of hydrometeorological disasters, this study aims to ensure that the community remains alert and prepared to face potential hazards in their environment, enhances their ability to withstand threats, and strengthens their overall resilience.